Poverty eradication, land development and forest resource utilisation among the orang asli in peninsular Malaysia / Lim Hin Fui - Lim, Hin Fui (2004)
This paper examines the implementation of land schemes on poverty eradication and forest resource utilisation by the Orang Asli in Peninsular Malaysia. One case study in Bukit Serok Regroupment Scheme in Pahang showed that when commercial land development program took place, Orang Asli responding to this new form of agricultural development have benefited in many ways, enjoying the basic facilities (road, school, clinic, water and electricity supply) and experiencing better living standards. In the meantime, agricultural modernization and development has reduced the degree of forest dependence in sustaining their daily livelihood. Another case study in Air Banun Regroupment Scheme in Perak indicated a different situation. As the land issue regarding the regroupment scheme is yet to be resolved by the federal and state governments, commercial agricultural development is lukewarm. Faced with a lack of regular source of income from commercial agriculture, the regrouped Orang Asli have little choice but to continue depending on non-timber forest products (NTFP) for livelihood. NTFP dependence does not provide the desired regular yield and source of income. Consequently, their living standard leaves much to be desired. These two case studies showed that to achieve the national goal of poverty eradication among the Orang Asli and to conserve the biodiversity in the forests, commercial agricultural land development is essential for the regrouped population. The development of oil palm and rubber provides a new form of employment and a more regular source of income for Orang Asli. On the other hand, without proper agricultural development program, the Orang Ash would continue to depend on the forest resources to sustain their livelihood thus adding pressure to the sustainability of non-timber forest resources. While their ties with the forest remain they are also trapped in the vicious circle of poverty.